DEVELOPMENT OF DEFORMATION STRIPS WHILE STRETCHING OF CYLINDRICAL SAMPLES - Y. V. Vasilevich; E. A. Moiseichik; A. M. Yaznevich (Наука и техника)
Deformation strips have been experimentally revealed and described while stretching of cylindrical samples by means of computer thermography. It has been established that temperature of shift strip surface grows smoothly up to the stage of crack origin in material defect. Sharp growth of surface temperature occurs when tensile stresses reach tensile strength. Change in surface temperature occurs wavy after destruction (while cooling the sample). Processes of material destruction origin and development  characterize temperature changes in deformation strips.